PEMBUATAN MASKER WATERPROOF BERBAHAN POLYESTER UNTUK MENCEGAH PENULARAN DROPLET BAKTERI DAN VIRUS DALAM UPAYA PEMUTUSAN MATA RANTAI PENULARAN COVID-19 - Seprianto Seprianto; Molani Paulina Hasibuan; Ratih Permana Sari (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The Covid-19 pandemic has plagued almost all parts of the world. The virus is transmitted by droplets, droplets, or in medical terms known as droplets when someone coughs, sneezes, or talks. There are two ways of transmitting the corona virus through droplets, namely directly and indirectly. The use of masks in preventing direct transmission of the virus is an important thing to do. Making waterproof masks made from polyester fabrics that are waterproof, splash or droplet seepage is an alternative for people to get proper masks without having to spend a lot of money. The use of a waterproof mask made from polyester cloth is not only more economical, but also more environmentally friendly because it can be reused. The simple manufacturing process and easy and inexpensive materials allow this business to be accepted by the community. This waterproof mask making training can improve the readiness of the people of Langsa City, especially Lhokbanie Village, to face the Covid-19 pandemic. The mask products produced from this training can also be used repeatedly so that they can protect the environment.